Building a model of the process of shaping tapered calibrating areas of wheels at the two-sided grinding of round ends - Kalchenko, Volodymyr; Kalchenko, Vitalіі; Kolohoida, Antonina; Kalchenko, Olga; Kalchenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports the spatial modeling of the dressing process of grinding wheels with a conical calibration area to enable two-sided end grinding of cylindrical parts. Components with cylindrical end surfaces are common in the industry, for example, bearing rollers, crosses, piston fingers, and others. High requirements are put forward for the accuracy and quality of the end surfaces. The most efficient is to machine them simultaneously on a double-sided face grinding machine. To improve the quality, grinding is carried out by oriented wheels. The wheel’s angle of rotation in the vertical plane is chosen subject to the uniform distribution of the allowance along a working surface; this makes it possible to reduce the temperature in the cutting zone and improve machining conditions. To improve the accuracy, grinding wheels are provided with a conical calibration area whose rectilinear generatrix is in the plane passing through the axis of wheel rotation and is perpendicular to the end of the part. The minimum permissible length of the calibration area depends on the diameter of the parts being machined; that makes it possible to utilize the work surface more efficiently. Two wheels are dressed simultaneously using diamond pencils that are symmetrically installed in a part feed drum. The angular velocity when dressing the rough area of the wheel is constant, which ensures its different development, and it gradually decreases when dressing the calibration area to provide for its constant roughness. In general, this prolongs the resource of grinding wheels and the quality of machining. The wheels are given axial movement to ensure the straightness of the cone calibration area. The dressing technique reported here can be used on machines equipped with a numerical software control system and without it. It could also be applied in the machining of parts with non-round ends